2015
DOI: 10.1080/10503307.2015.1051163
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method investigation of patient monitoring and enhanced feedback in routine practice: Barriers and facilitators

Abstract: Objective: To investigate the barriers and facilitators of an effective implementation of an outcome monitoring and feedback system in a UK National Health Service psychological therapy service. Method: An outcome monitoring system was introduced in two services. Enhanced feedback was given to therapists after session 4. Qualitative and quantitative methods were used, including questionnaires for therapists and patients. Thematic analysis was carried out on written and verbal feedback from therapists. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 44 publications
(56 reference statements)
3
43
0
1
Order By: Relevance
“…While most ROM studies have focused on a single patient‐therapist dyad, psychiatric hospitals tend to use a multidisciplinary approach, involving multiple therapists (eg, a psychiatrist and psychologist), multiple modalities (individual and group therapy), and at times multiple patients (eg, family interventions). We concur with other researchers who have previously highlighted this obstacle in complex large sites such as mental health hospitals . One proposed solution was to measure outcomes only in the main therapy while assessing the working alliance in all other modalities.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…While most ROM studies have focused on a single patient‐therapist dyad, psychiatric hospitals tend to use a multidisciplinary approach, involving multiple therapists (eg, a psychiatrist and psychologist), multiple modalities (individual and group therapy), and at times multiple patients (eg, family interventions). We concur with other researchers who have previously highlighted this obstacle in complex large sites such as mental health hospitals . One proposed solution was to measure outcomes only in the main therapy while assessing the working alliance in all other modalities.…”
Section: Discussionsupporting
confidence: 87%
“…The increasing use of ROM over the past decade has fostered many discussions related to challenges and obstacles of outcome measurement implementation, producing many experience‐drawn conclusions to learn from . Simultaneously, it is well acknowledged that different countries and mental health facilities have different obstacles to face while attempting implementation . In this article, we report on the first systematic and elaborative effort to widely assimilate the use of empirical measurements in the daily routine of a large, active and hectic, mental health hospital in Israel, while facilitating the elaboration of ROM feedback reports into its clinical work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that their design was "the most suitable and comprehensive approach to ascertain the effectiveness of the interventions whilst also gathering participants' views on the intervention" (Lopez et al, 2014, p. 412). Similar findings emerged in other studies where qualitative data were indicated to have deepened the findings by going beyond statistical testing (e.g., Finucane & Mercer, 2006;Grocke et al, 2014;Herrera-Mercadal et al, 2015;Lucock et al, 2015;Lucre & Corten, 2013;Robinson, McCague, & Whissell, 2014;Werbart et al, 2015). This reinforces the value derived from speaking with participants to better conceive the fruitfulness of interventions.…”
Section: Integration Of Clients' Perceptions Via Mixingsupporting
confidence: 86%
“…An important concern generally remains the implementation and the integration of ROM in clinical practice [26,[78][79][80]. ROM feedback can be considered as a communication tool, and research showed that ROM feedback discussions have a positive effect on treatment cooperation [81].…”
Section: Clinical and Research Recommendations For Use Of Rom In Treamentioning
confidence: 99%